Isolated Pancreatic Tuberculosis Mimicking Focal Pancreatitis and Causing Segmental Portal Hypertension - Rana, Surinder S; Bhasin, Deepak K; Rao, Chalapathi; Singh, Kartar (JOP. Journal of the Pancreas, 2010)
Context Isolated pancreatic tuberculosis is a common mimicker of pancreatic malignancy and a common presentation is abdominal pain. However, segmental portal hypertension is very uncommon. Case report A case of isolated pancreatic tuberculosis mimicking focal pancreatitis and causing segmental portal hypertension is presented. Conclusion A histological or microbiological diagnosis of the presence of pancreatic masses is necessary to detect potentially treatable diseases, such as tuberculosis, in endemic countries like India. Image: CECT showing the bulky head and body of the pancreas with heterogeneous areas of non-enhancement suggestive of necrosis and peripancreatic fat stranding.